2021
DOI: 10.3390/buildings11030111
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofitting Resilience-Based for Strategic RC Buildings

Abstract: The resilience of communities is given by the ideal convolution of the resilience of all their single parts. Strategic buildings require high levels of performance during and after a seismic sequence. Consequently, the seismic retrofitting of old strategic buildings is a central issue in prevention and mitigation strategies. The core of the study is a resilience approach to the seismic retrofitting of existing strategic buildings. Different performance levels are considered and four different retrofitting tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Based on previous experiences, the 2016 earthquake, Italy started to work on surveying the buildings that was built with non-seismic design codes and proceed with the structural consolidation with classic techniques like adding reinforced concrete walls and steel jackets, or modern techniques like seismic isolation systems (Vona et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous experiences, the 2016 earthquake, Italy started to work on surveying the buildings that was built with non-seismic design codes and proceed with the structural consolidation with classic techniques like adding reinforced concrete walls and steel jackets, or modern techniques like seismic isolation systems (Vona et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The approach must be based on the integration of all the requirements. An optimal retrofit strategy must be considered for the use and reuse of RC buildings and civil engineering works, following well-known multi-criteria schemes [42,43] and resilience concepts [44].…”
Section: Methodological Approach For Retrofittingmentioning
confidence: 99%
“…As far as the economic aspect is concerned, in cases similar to the case study, the seismic isolation system has already shown its convenience compared to other systems [24,37].…”
Section: Estimation Of the Transformation Costsmentioning
confidence: 99%